A plea for visual inquiry. Issue 3 (2nd October 2022) - Hermans, Peter; Schönau, Diederik
Abstract: This contribution is intended as a plea for the reappraisal of drawing as a means of active visual inquiry in Visual Literacy. Active visual inquiry is a most adequate concept to describe the first two phases of the sub-domain of 'producing' in the revised Common European Framework of Reference for Visual Competency (CEFR-VC): 'the competency to generate visual ideas' and 'the competency to do visual research'. It also relates to activities covered by the first two phases of the sub-domain of 'responding' in the CEFR-VC: the 'competency to perceive images with an open mind' and 'the competency to explore images'. All four competencies rely on ways of visual thinking, visual analysis and understanding of images in visual terms. They suggest that learning in the visual domain should be compulsory for all students in education. These competencies and their underlying skills were paramount in art education before World War II. Since then we have witnessed a gradual marginalization of these competencies – in particular technique and repertoire – in favour of interests in content, communication and creativity. We think it is time to address the neglect of these competencies and make a plea for active visual inquiry through drawing to be given a more prominent place in visual literacy education than it is given now.